A Select library of the Nicene and post-Nicene fathers of the Christian church - Augustine; John Chrysostom Saint, d. 407.; Schaff, Philip (The Christian Literature Co., 1886)
v. 1. The confessions and letters of St. Augustin, with a sketch of his life and work.--v. 2. St. Augustin's City of God and Christian doctrine.--v. 3. St. Augustin: On the Holy Trinity. Doctrinal treatises. Moral treatises.--v. 4. St. Augustin: The writings against the Manichæans, and against the Donatists.--v. 5. Saint Augustin: Anti-Pelagian writings.--v. 6. Saint Augustin: Sermon on the mount. Harmony of the Gospels. Homilies on the Gospels.--v. 7. St. Augustin: Homilies on the Gospel of John. Homilies on the First epistle of John. Soliloquies.--v. 8. St. Augustin: Expositions on the book of Psalms.--v. 9. St. Chrysostom: On the priesthood; Ascetic treatises; Select homilies and letters; Homilies on the statutes.--v. 10. St. Chrysostom: Homilies on the Gospel of St. Matthew.--v. 11. St. Chrysostom: Homilies on the Acts of the apostles and the Epistle to the Romans.--v. 12. St. Chrysostom: Homilies on the Epistles of Paul to the Corinthians.--v. 13. St. Chrysostom: Homilies on Galatians, Ephesians, Philippians, Colossians, Thessalonians, Timothy, Titus, and Philemon.--v. 14. St. Chrysostom: Homilies on the Gospel of St. John and the Epistle to the Hebrews.